2022
DOI: 10.3389/feart.2022.865989
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Tephra Fall and Sediment-Water Flows to Assess Their Impacts on a Vulnerable Building Stock in the City of Arequipa, Peru

Abstract: Arequipa, Peru’s second economic center hosting c. 1,110,000 inhabitants, is the largest South American city exposed to a large variety of natural hazards. At least 200,000 live in areas likely to be affected by hazards from El Misti volcano, located 17 km to the NE. A multidisciplinary project aims to address the impacts of tephra fall and frequent mass flows on the vulnerable building stock and roofs along two ravines that cross the city, enabling decision-makers to undertake retrofitting projects and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(134 reference statements)
0
0
0
Order By: Relevance
“…In terms of local impact in the Pollena case study (the largest one), while most of the calculated points (44) fall in the range of lahar velocity of 2-4 m/s and dynamic pressure of 4-8 kPa, a few peak values of velocity of 13-15 m/s and dynamic pressure of 90-115 kPa are also calculated, which are directly related to meter-sized clasts entrained into the lahars on the steep slopes, then deposited downstream of alluvial fans. Such values of the velocity and dynamic pressure are well comparable with those calculated for lahars that occurred recently at Ruapehu in 2007 (Lube et al, 2012) and Merapi in 2011 (Jenkins et al, 2015), and in historical times at El Misti (Thouret et al, 2022). In particular, the estimated velocities and pressure agree with those of Lube et al (2012) and Jenkins et al (2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In terms of local impact in the Pollena case study (the largest one), while most of the calculated points (44) fall in the range of lahar velocity of 2-4 m/s and dynamic pressure of 4-8 kPa, a few peak values of velocity of 13-15 m/s and dynamic pressure of 90-115 kPa are also calculated, which are directly related to meter-sized clasts entrained into the lahars on the steep slopes, then deposited downstream of alluvial fans. Such values of the velocity and dynamic pressure are well comparable with those calculated for lahars that occurred recently at Ruapehu in 2007 (Lube et al, 2012) and Merapi in 2011 (Jenkins et al, 2015), and in historical times at El Misti (Thouret et al, 2022). In particular, the estimated velocities and pressure agree with those of Lube et al (2012) and Jenkins et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…where a > 0 depends on clast properties, and its square has dimension of pressure. On the other hand, it is not straightforward to constrain local flow velocities with unique values of flow densities, mostly because small variations of velocity correspond to large variations of density, and this is particularly valid for volcaniclastic mass flows (Carling, 2013;Jenkins et al, 2015;Roche, 2015;Martí et al, 2019;Guzman et al, 2020;Thouret et al, 2022). At some locations in the study area, we found lahar deposits against meter-scale manufacturing obstacles (Di Vito et al, 2009).…”
Section: Appendix a Calculation Of Lahar Velocities And Dynamic Press...mentioning
confidence: 92%
“…), and it is able to calculate the advection of additional variables (density and temperature) in modified versions. From its beginning to the present, Vol-cFlow has been successfully used for simulating debris avalanches [80,[122][123][124][125], pyroclastic flows [81,126], tsunamis [127], and lava flows [33,52,128]. Additionally, it has provided very accurate and fast results in benchmark tests [21,67,68], and it is very well documented that it is very well balanced in terms of complexity and usability.…”
Section: Numerical Approach and Simulation Of Lava Flowmentioning
confidence: 99%
“…Debido a la ocupación antrópica, no había un cauce definido, lo que afectó las asociaciones de vivienda El Mirador, La Florida y San Pedro, así como al mercado principal y la terminal terrestre de Tacna, que se encuentran en la zona baja (Instituto Geológico Minero y Metalúrgico [INGEMET], 2020). Según afirma Thouret et al (2022), el evento repentino se produjo debido al entorno árido o semiárido, donde la lluvia se acumuló en un corto lapso y el suelo tenía poca capacidad para absorberla, lo que resultó en un rápido escurrimiento en las pendientes pronunciadas poco después de que comenzó la lluvia.…”
Section: Introductionunclassified